Enabling digital participation in Higher Education - Anita Reardon; David Kane; Jonathon Hickman (Educational Futures)
This paper reports on a research informed teaching project which explored the role of technology in the delivery of the Secondary Post Graduate Certificate of Education (PGCE) at Birmingham City University. Our study highlights the problematic nature of imposing a set of normative uses of technology within teaching and learning and suggests that the student voice has an important role to play in shaping innovation.